Role Of Mycorrhiza-Trichoderma and Anorganic Fertilizer on Growth, Yield and Vitamin C of Cauliflower - Eny Rokhminarsi; Darini Sri Utami; Wilis Cahyani; Okti Herliana (Jurnal Hortikultura Indonesia, 2022)
Cauliflower is a potential vegetable commodity because it contains vitamins and minerals. Cauliflower cultivation needs to be expanded to marginal lands such as Ultisol. The aim of this research was to determine the dosage of mycorrhiza-Trichoderma with reduced anorganic fertilizer on the growth, yield, and vitamin C content of cauliflower in ultisol. This research was carried out on experimented pots using a factorial completely randomized block design, and three replications. The first factor is mycorrhiza+Trichoderma combinations is 0 g + 0 g, 10 g + 10 g, and 20 g + 20 g; the second factor is anorganic fertilizer reduction (urea, SP36, and KCl) from the recommended dosages is 0%, 25%, and 50%. The data were analyzed using F-test and DMRT. The research results showed that 20 g mycorrhiza+20 g Trichoderma plant-1 increased the infection percentage of mycorrhiza up to 56.7% when compared to 10 g mycorrhiza-10 g Trichoderma. The best combination with the highest plants was obtained without mycorrhizal-Trichoderma with a 25% reduction of anorganic fertilizer, while the highest dry root weight on 10 g mycorrhiza + 10 g Trichoderma with 50% anorganic fertilizer. The highest yield (curd) was obtained at 20 g mycorrhiza + 20 g Trichoderma with a 25% reduction in anorganic fertilizer, while the highest vitamin C content was obtained at 20 g mycorrhiza + 20 g Trichoderma with a 50% reduction of anorganic fertilizers. Keywords: biofertilizer, vegetables, cultivation, marginal land